(untitled) (Global Journal of Human-Social Science, 2024)
The rise of hooliganism in Soviet Belarus populous areas between 1953 and 1968 constituted a significant threat to public order Hooligans disrespected the legal underpinnings of the Soviet state the rights of individuals and the capacity of the inhabitants to rest well after a stressful day Hooligans terrorized lone people during the night damaging and breaking benches fences plants and lanterns They also drank alcohol sang loudly and spoke making it difficult for neighbors to sleep Their false sense of superiority over hooligans victims boosted their self-esteem The Belarusian Military District s service members engaged in specific forms of hooliganism against the general populace After the Gulag was dismantled a large number of prisoners were released from prison in part due to the rise in hooligan activity Hooligans were frequently the result of youthful maximalism legal nihilism and domestic instability Due to the aftermath of World War II a large number of children were raised in singleparent households where the mother worked long hours without giving the next generation the care it needed Oral traditions musical works with criminal content and the cult of thieves romance also had a negative impact To counteract this phenomenon legislative measures were implemented and internal affairs authorities made extensive use of preventive measures including the Voluntary People s Guard and tougher prosecution There were serious problems with the legal system that made it impossible to completely address the hooliganism issues on Soviet Belarusian territory These issues included poorly thought-out reforms inadequately trained personnel a lack of leisure time for young people the spread of alcoholism and outdated infrastructure